2022
DOI: 10.1021/acsaem.2c00819
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene–Perylenediimide Bridged Dimeric Porphyrin Donors Based on the Donor–Acceptor–Donor Structure for Organic Photovoltaics

Abstract: Two D–A–D (D = donor, A = acceptor)-based small-molecule donors, TPDI-2P and F-TPDI-2P, are designed and synthesized for organic solar cells (OSCs), with two strong donor porphyrin units bridged by either an electron-deficient diethynyl-substituted thiophene–perylenediimide (TPDI) linker for the former or a diethynyl-fused TPDI linker for the latter; 3-ethylrhodanine units were then flanked symmetrically by phenylenethynylene π-linkers. Both compounds show strong absorption profiles from 400 to 800 nm, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…10 Zhu et al developed two triads featuring fulleropyrrolidine−perylene tetracarboxylicdiimide−freebase porphyrin (FPP) and its zinc derivative (ZnFPP) for organic solar cells with a device efficiency of 0.35%. 11 The absorption and redox properties of these triads suggested that there exist ground-state electronic interactions in these triads, and emission properties indicate that there was an efficient photoinduced electron transfer (PET) from porphyrin to C 60 . 38 In another study, Giribabu et al, have reported a triad system in which phenothiazine is the primary donor, porphyrin is the secondary donor, and thiophene cyano acrylic acid is an acceptor for dye-sensitized solar cell application, in which the device efficiency was >10%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Zhu et al developed two triads featuring fulleropyrrolidine−perylene tetracarboxylicdiimide−freebase porphyrin (FPP) and its zinc derivative (ZnFPP) for organic solar cells with a device efficiency of 0.35%. 11 The absorption and redox properties of these triads suggested that there exist ground-state electronic interactions in these triads, and emission properties indicate that there was an efficient photoinduced electron transfer (PET) from porphyrin to C 60 . 38 In another study, Giribabu et al, have reported a triad system in which phenothiazine is the primary donor, porphyrin is the secondary donor, and thiophene cyano acrylic acid is an acceptor for dye-sensitized solar cell application, in which the device efficiency was >10%.…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of sunlight into different forms of energy by following natural or artificial photosynthesis paths is an attractive and fascinating topic that has inspired researchers in physics, chemistry, and biology. Photosynthesis exemplifies a remarkable model that has inspired the design of numerous complex assemblies to translate light energy into chemical potential. A great variety of donor–acceptor (D–A) systems have been reported in the literature to understand photoinduced events and the underlying mechanisms. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have shown a keen interest in extending the π-conjugation of porphyrin dimers with electron-deficient units such as diketopyrrolopyrole, perylenediimide, and benzothiadiazole or electron-rich benzodithiophene, diethynylenedithio-phene, and diethynylenephenylene as linkers. As-prepared SMs as donors showed higher molar absorption coefficients, wider absorption bands, excellent thermal stabilities, and suitable redox potentials in comparison to porphyrin monomers; as a result, the PCEs of OPVs reached over 10%. However, there is an apparent weak absorption between the Soret and Q-bands of porphyrins at around 550–700 nm, which causes an inefficiency in generating sufficient photon absorption, resulting in low short-circuit currents ( J SC ) in OPVs.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The D-A strength, which is dependent on the type of donor group, acceptor group as well as the type of p-linker/spacer unit, plays a significant role in the development of D-A systems. 17 D-A chromophores with a low bandgap exhibit potential applications in DSSCs, 18 bulk heterojunction organic solar cells (BHJOSCs), 19 NLOs, 20 organic field effect transistors (OFETs), 21 bioimaging 22 and photodynamic therapy. 23 1.1.…”
Section: Introductionmentioning
confidence: 99%